Forêt et conservation des dunes littorales : le cas exemplaire de la Réserve biologique domaniale de la Côte d'Opale (Pas-de-Calais) - Yves Petit-Berghem (EchoGéo)
The coastal dunes of the Pas-de-Calais area (dunes of Berck-Merlimont with the « Réserve biologique domaniale de la Côte d’Opale », northwest France) is one of the few dune systems in France characterized by the free expression of dynamic processes. The mobility of the site ensures the renewal and diversity of dune environments and thus habitats and species associated with them. Like any reserve, it is a regulated area where management actions are oriented in one direction (conservation management) and strictly controlled. The challenge for managers today is to define a longer-term objective of this reserve. What are the working partners for which it would be possible to collaborate? What degree of openness to the public? What are the research topics to develop? How to reconcile a policy of environmental conservation with sustainable territorial development? These questions require a discussion between nature and society and return to the governance of the territories and the place of man in his environment.